Sphingosine–sphingosine-1-phosphate pathway regulates trophoblast differentiation and syncytialization - Singh, A.; Dharmarajan, Arunasalam; Aye, I.; Keelan, J. (Elsevier, 2012)
Sphingosine and sphingosine-1-phosphate (S1P) are involved in regulating cell differentiation. This study postulated that changes in sphingolipid biosynthesis and metabolism are important in trophoblast syncytialization and therefore examined the production, metabolism and actions of sphingosine and S1P during spontaneous trophoblast differentiation and fusion in vitro. Significantdeclines in intracellular sphingosine concentration (P 0.05) and sphingosine kinase 1 (SPHK1) expression (P 0.01) were observed during trophoblast syncytialization. Secreted S1P concentrations dropped steeply after 72 h, before rising to basal concentrations with syncytialization. Intracellular S1P concentrations were undetectable throughout. Treating cells with exogenous sphingosine (P 0.01), S1P (P 0.001) or a specific SPHK1 inhibitor (P 0.05) for up to 72 h in culture significantly inhibited trophoblast differentiation (measured as reduced human chorionic gonadotrophin production); effects on other biochemical and morphological markers of differentiation were absent or inconsistent. Phosphorylation of Akt, an established down-stream target of S1P that spontaneously declines with trophoblast differentiation, was markedly reduced by S1P (P 0.05). In conclusion, changes in the sphingosine–S1P pathway are involved in the regulation of trophoblast differentiation in term human placenta. Dysregulation of sphingolipid homeostasis could, therefore, disrupt placental formation and function with deleterious consequences for pregnancyoutcome.